Estimation of forest chemical energy content in tropical rainforest area using airborne lidar - Mohd. Asraff Asmadi, 1992-, author; Muhammad Zulkarnain Abd. Rahman, supervisor; Fakulti Geoinformasi dan Harta Tanah (2015)
Project Paper (Sarjana Muda Sains (Geoinformatik)) - Universiti Teknologi Malaysia, 2015